Clinical Observation on Removal of Small Foreign Bodies Touching the Optic Nerve in the Deep Orbital Region: A Case Series. (24th February 2014) - Tian, Yan-Ming; Gao, Xiao-Wei; Ren, Bing; Ju, Yan; Li, Peng; Qiao, Lei; Yan, Xi-Dong
Abstract: Purpose : Five patients presented to our institution with deep intraorbital foreign bodies adjacent to the optic nerve. We removed all foreign bodies by lateral orbitotomy to evaluate the treatment and the benefits of their extraction. Methods : The clinical outcomes of the five patients were retrospectively analyzed. Results : Radiology in all five patients revealed small foreign bodies touching the optic nerve in the deep orbital region. All patients also suffered from significant secondary psychological disturbances, these including anxiety and altered sleep patterns. They had become preoccupied with a strong desire to remove the intraorbital foreign bodies [IFB]. In this cohort, two had no light perception before surgery, another two had light perception, and one had hand motion perception as well as vitreous hemorrhage that had been plugged with silicone oil in other hospital. All foreign bodies were removed via lateral orbitotomy. Visual acuity improved after the operation in only three cases. However, the psychological well-being of all five patients improved. Conclusions : Consideration should be given to removal of intraorbital foreign bodies adjacent to the optic nerve, even where a significant degree of vision has already been lost. Furthermore some patients can achieved vision improvement and such surgery can frequently address the significant psychological disturbance that can be associated with such orbital foreign bodies.